Ethics for Laboratory Medicine. - Gronowski, Ann M.; Budelier, Melissa M.; Campbell, Sheldon M. (Clinical Chemistry, 2019)
BACKGROUND: Laboratory medicine, like other areas of medicine, is obliged to adhere to high ethical standards. There are particular ethical issues that are unique to laboratory medicine and other areas in which ethical issues uniquely impact laboratory practice. Despite this, there is variability in ethics education within the profession. This review provides a foundation for the study of ethics within laboratory medicine. CONTENT: The Belmont Report identifies 3 core principles in biomedical ethics: respect for persons (including autonomy), beneficence (and its corollary nonmalfeasance), and justice. These core principles must be adhered to in laboratory medicine. Informed consent is vital to maintain patient autonomy. However, balancing patient autonomy with the desire for beneficence can sometimes be difficult when patients refuse testing or treatment. The use of leftover or banked samples is fundamental to the ability to do research, create reference intervals, and develop new tests, but it creates problems with consent. Advances in genetic testing have created unique ethical issues regarding privacy, incidental findings, and informed consent. As in other professions, the emergence of highly contagious and deadly infectious diseases poses a difficult ethical dilemma of helping patients while protecting healthcare workers. CONCLUSIONS: Although many clinical laboratorians do not see or treat patients, they must be held accountable to the highest ethical and professional behavior. Recognition and understanding of ethical issues are essential to ethical practice of laboratory medicine.